2021
DOI: 10.3390/jcm10081578
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical In Vivo Modeling of Pediatric Sarcoma—Promises and Limitations

Abstract: Pediatric sarcomas are an extremely heterogeneous group of genetically distinct diseases. Despite the increasing knowledge on their molecular makeup in recent years, true therapeutic advancements are largely lacking and prognosis often remains dim, particularly for relapsed and metastasized patients. Since this is largely due to the lack of suitable model systems as a prerequisite to develop and assess novel therapeutics, we here review the available approaches to model sarcoma in vivo. We focused on genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 199 publications
(168 reference statements)
0
19
0
Order By: Relevance
“…Currently available preclinical models of RMS include conventional cell lines, various genetically engineered animal models (GEMs), as well as patient‐derived xenograft models (PDX or O‐PDX when transplanted orthotopically; Kashi et al , 2015; Imle et al , 2021). Each of these systems possesses specific benefits and drawbacks, resulting in suitabilities for different research questions or stages in drug development (Kim et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Currently available preclinical models of RMS include conventional cell lines, various genetically engineered animal models (GEMs), as well as patient‐derived xenograft models (PDX or O‐PDX when transplanted orthotopically; Kashi et al , 2015; Imle et al , 2021). Each of these systems possesses specific benefits and drawbacks, resulting in suitabilities for different research questions or stages in drug development (Kim et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PDX models are highly predictive of clinical treatment response. 260 This is evident in the response rates to standard chemotherapeutic and targeted therapies in PDX models correlating well with clinical outcome for a number of cancer patients including those with colorectal, pancreatic, non-small cell lung and breast cancer. [261][262][263][264][265] Several studies have reported successful establishment of STS and bone sarcoma PDX models, with an overall engraftment success rate of 32-69% and successful recapitulation of the genetic and phenotypic characteristics of the original tumor.…”
Section: Personalized Precision Medicinementioning
confidence: 94%
“…Currently available preclinical models of RMS include conventional cell lines, various genetically engineered animal models (GEMs), as well as patient-derived xenograft models (PDX or O-PDX when transplanted orthotopically) (Imle et al, 2021; Kashi et al, 2015). Each of these systems possesses specific benefits and drawbacks, resulting in suitabilities for different research questions or stages in drug development (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%